Value Conflict of Character Education in Traditional Pesantren - Abdul Kholiq (Nadwa: Jurnal Pendidikan Islam, 2022)
The ghasab (taking or using someone's belonging without permission) phenomenon in pesantren has become the 'dark side' amidst its image as a center of religious education (taffaquh fiddin). It may not only affect the mental and personality development of santri, but also damage the image of the pesantren. This study aimed to investigate the practice of ghasab in pesantren and explore how moral conflicts in moral judgment occur in santri. This study was conducted at two traditional pesantrens in Semarang and incorporated descriptive qualitative methods. The data were collected through in-depth interviews and observation. The finding indicated that pesantren's communal life system brought consequences for the practice of ghasab among santri. However, it cannot be generalized as a common culture in all pesantren. It was also found that this phenomenon was influenced by internal and external factors of pesantren environment and had the potential to cause value conflicts that affected the moral judgment of santri. Therefore, the commitment of pesantren management is needed to reaffirm its mission as a center for building religious student characters who have integrity.